THE USE OF VOCABULARY JOURNAL IN TEACHING VOCABULARY - Elita, Nur; Sutapa, Y. Gatot; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was aimed at discovering the effect of vocabulary journal on students? vocabulary achievement on the eighth grade students of SMP Negeri 2 Teluk Keramat in academic year 2016/2017. This research was pre-experimental research with one group pre-test post-test design. The population of this research was the eighth grade students of SMP Negeri 2 Teluk Keramat in academic year 2016/2017 with the total number of students were 131 students and the sample of the research was class VIII B which consisted of 33 students. The measurement technique was employed to collect the data. Based on the result of the hypothesis testing as well as analysis of the effect size, the use of vocabulary journal has a strong effect in teaching vocabulary on descriptive text in SMP Negeri 2 Teluk Keramat. Vocabulary journal enabled the students to learn vocabulary actively, made the students more aware of learning vocabulary, and it can be used to review the material. It was indicated by the improvement of the students? vocabulary achievement after getting three times treatments by the implementation of vocabulary journal. Referring to research finding, the researcher recommends this technique to be implemented, especially in teaching vocabulary. Keywords: Vocabulary Journal, Teaching Vocabulary, Vocabulary Achievement.